Landmark Constitutional Cases that Changed South Africa - Laubscher, Roxan (UJ Press, 2023)
On 14 February 1995, the Constitutional Court of South Africa was inaugurated by President Nelson Mandela. In his inaugural speech, President Mandela remarked that the "future of our democracy" hinged on the existence and the work of the newly created Constitutional Court. Furthermore, President Mandela rightly asserted that it is the Constitutional Court's task "to ensure that the values of freedom and equality which underlie our interim constitution - and which will surely be embodied in our final constitution - are nurtured and protected so that they may endure". These sentiments are as true now as they were almost thirty years ago. However, whether and how the courts have nurtured and protected these sentiments over the last twenty-eight years is the topic that we want to address. This book serves as the first volume in a series of books that considers selected landmark judgments of the South African Constitutional Court.